INHIBITORY EFFECT OF ETHANOLIC EXTRACT OF ERIOBOTRYA JAPONICA LEAVES PRE-INCUBATED WITH THEOPHYLLINE AND ASPIRIN ON ISOLATED GUINEA PIG TRACHEAL - Marianne; Harahap, Urip; Salim, Emil; Irfan Husori, Dadang; Jali Rambe, Fahrumsyah; Kristiani, Noni (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of the study were to examine the inhibitory effect of ethanol extract of Eriobotrya japonica leaves (EEEJL) pre-incubated with theophylline and aspirin on isolated guinea pig tracheal chains against acetylcholine (ACh)-induced contraction. Methods: The effect of EEEJL (1-8 mg/Ml) on the isolated tracheal strips was tested in vitro. Furthermore, the mechanism of relaxant effects of EEEJL was evaluated in the presence of theophylline and aspirin. Results: The contractile response evoked by Ach (1.25 × 10−3 M) was decreased by EEEJL (effective concentration50 = 1.36 mg/mL) and has no significant difference of relaxant effect to that of EEEJL pre-incubated with theophylline and aspirin (p>0.05). Conclusion: The EEEJL decreased the ACh-induced contraction through the inhibition of PDE and the protective effect on prostaglandin E2.